Methods of public management in the National police of Ukraine: a general theoretical approach - K. L. Buhaichuk (Law and Safety)
The author of the article has studied general theoretical approaches to the content of the term of «method of activity». Based on the research of scientific works on the theory of state governance, administrative law, administrative management, public management, the author has formulated own definition of the concept of «methods of public management within the agencies of the National Police of Ukraine», which are methods and approaches of authoritative and management influence management applied by authorized entities within their competence aimed at streamlining the organizational structure of the system of the National Police of Ukraine, planning, preparation, development, execution and implementation of management decisions, organization of the work of the management apparatus, implementation of documentary, informational, personnel, psychological provision of the activities of the agencies and units of the National Police.